Analysis Of The Corelation Between Risk Factors And The Incidence Of Early Postpartum Hemorrhagia - Mayasari, Dian; Utami, Dian Asih Ning; Marlina, Raini (Jurnal Keperawatan Profesional, 2025)
Postpartum hemorrhage can be influenced by the presence of risk factors during the antenatal period and risk factors during the intrapartum period. Although postpartum hemorrhage can occur unexpectedly, several studies explain that there are risk factors that can be modified or managed with extra vigilance. The purpose of this study was to determine the relationship of risk factors consisting of maternal age, parity, birth spacing, number of antenatal check-ups, delivery history, iron supplementation and twin pregnancies with the occurrence of early postpartum hemorrhage. This study used a quantitative cross-sectional design approach. The population was all postpartum mothers at the Kembang Janggut Community Health Center, Kutai Kartanegara Regency. The sample size was 30 postpartum mothers who met the sampling criteria with a purposive sampling technique. Data collection used interviews and questionnaires by postpartum mothers. Data analysis using Chi-square. The results of the study showed that there was a significant relationship between maternal age, parity, birth spacing, number of antenatal check-ups, delivery history, iron supplementation, and twin pregnancies with the incidence of early postpartum hemorrhage with the results of the chi-square analysis test obtained a p value <α (0.05). Efforts to prevent early postpartum hemorrhage need to be carried out as much as possible by improving services, counseling, and increasing training of health workers to improve competence in early detection and prevention of postpartum hemorrhage